How do green HRM practices affect employees' green behaviors? The role of employee engagement and personality attributes - Ababneh, Omar Mohammed Ali (Journal of environmental planning and management, 2021)
This study suggests a novel progress in the change journey toward sustainability by empirically investigating the mediation role of employee engagement with environmental initiatives between green HRM practices and individual green behavior. Further, this study invoked the classical theory of person-organization-fit to examine the role of certain personality traits in moderating the associations between HRM practices and employee engagement with environmental initiatives. A quantitative research method with a purposeful-sampling technique was used to reach 376 employees who work at four and five-star hotels operating in Jordan. The study provides original findings indicating that employee engagement partially mediates the association between green HRM practices and individual green behavior. Additionally, this study emphasizes the importance of organization-person interaction in fostering employee engagement with environmental initiatives.